Effectiveness of women managers in Iloilo City - Arriola, Anna Grace; Condez, Janis May.; Grasparil, Diadem Pearl; Libron, May.; Millamena, Rica Iris. (2000.)
Executive summary - This study aimed to describe women's status in the workplace as their capacity to perform managerial functions is being questioned by a patriarchal society. Education plays a significant role on the gradual transfromation of women's role. Today, women are enjoying the freedom of expressing themselves that they too are capable of performing and assuming responsibilities. Twenty women in Iloilo City had been randomly selected together with seventy-four employees to evaluate or assess their effectiveness in handling responsibilities as leaders and prime movers of their respective organizations. Methods used in gathering data were through questionnaires and personal interviews. The findings prove that gender is not a major issue in assuming top-level positions in the workplace. Women managers are viewed as approachable, understanding and considerate in running the organization and dealing with subordinates. They also excel in performing managerial functions especially in leading. From these findings, it is concluded that women are capable and effective in handling responsibilities and in making critical decision. For women managers to enhance their effectiveness, it is recommended that they should be proactive and responsive to employees' needs and wants. They should also be flexible to adapt to the changing environment, both internal and external.
Research Paper (Mgt 200 - Business Research) -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 2000.